Oral Placement Test as the Indicator of Bilingual Students’ Speaking Skills - Hanifah Hifni; Nida Husna; Didin Nuruddin Hidayat (Jurnal Studi Guru dan Pembelajaran, 2021)
This study investigates whether there is a significant relationship between the speaking ability of students in bilingual classes and their daily conversation performance, as reported in the oral placement test. The researchers analysed the relationship between the placement test scores and the speaking performance of 146 first-year bilingual students attending an Islamic Junior High School. An oral interview was applied to determine their speaking ability on the placement test and was conducted again to test their speaking ability at the end of the semester. Pronunciation, vocabulary, grammar, comprehension, and fluency were the scoring criteria for assessing the oral interview to indicate the learners’ English performance in speaking and their oral abilities. Each student is tested individually in more or less than ten minutes. A Pearson product-moment correlation coefficient was applied to determine the strength of the correlation between the oral placement test and those from the oral interview at the end of the semester. The data indicated that the results of the oral placement test when the students are still considered first-year students are still the same with their speaking at the end of the term; therefore, there is no significance and changes. These results turned out to be affected by the students’ learning style at the previous school, background knowledge, and the teacher’s teaching methods.